Orta Nitelikteki Konutlarda Banyo Mekanının İncelenmesi / Sevdim Anıl - Anıl, Sevdim (Fen Bilimleri Enstitüsü, 1995)
Bu çalışma da, insan vücudunun tümünün ya da belirli kısımlarının temizliğine ilişkin aktivitelerin içerisinde yer aldığı konut banyoları konu alanı olarak bellenmiştir. I. Bölümde, konuya giriş yapılmış ve ıslak mekanların konut ihtiyaç programındaki önemi vurgulanmıştır. E. Bölümde, banyo mekanının tanımı yapılmış, bu mekan içerisinde yer alan yıkanma-temizlenme eyleminin tarihsel içeriği incelenmiş ve bu eylemin analizi yapılmıştır. Banyo tasarım ilkelerinin belirlenmesi, ve banyo tasarımını etkileyen faktörler (kullanıcı özellikleri, mekan özellikleri ve eylem alanına ilişkin özellikler, sıhhi tesisat ekipman özellikleri ve yerleştirme ölçüleri) HI. bölümde ele alınmıştır. Tesisat sistemlerinin binada oluşturabileceği problemlerin belirlenmesi, ileride ortaya çıkabilecek sorunlara karşı erken önlem alınmasını kolaylaştıracağından, IV. bölümde sıhhi tesisat sistemlerinde planlama ve dizayn süreci ele alınmış ve sıhhi tesisat sistemlerine bağlı olarak ortaya çıkan sorunlar incelenmiş, hazır tesisat bileşenlerinin ıslak hacimlerde kullanılmasının önemine değinilmiştir. Orta nitelikteki 30 konut banyosunun incelenmesini içeren alan çalışması ve sonuçlan V. bölümde ele alınmıştır. Sonuç bölümünde ise, diğer bölümlerde yapılan araştırmaların ışığında, elde edilen sonuçlar ve öneriler yer almaktadır.

In house necessity program, wet volumes design (bath, etc.,.) which is included in the activities of cleaning lines off all human body or specific parts of body, have a special position. Applying the washing action in different forms; that depends on cultural, social, economical and technological structure through the human life, causes an important design problem of populations.Insufficiency of performance specifications and standards belonging to house wet places in our country cause packing or more place separation, moving of actions to other places, consequently unnecessary using of other places, loss of material, performance, energy, work force and finance in wet place applications. In order to provide the continuity of the building functionally, and ensure the needs related to health at optimum level, wet volumes and installation systems should be settled in a harmless way in design and in application, stage. Bath is a place, which ensures the purpose of health and care, at the same time in case of necessity, is used for washing actions and includes the combination of do§em-donat elements for this aim. The cleanliness actions in baths:1. For personal cleanliness and care who live in houses;-Taking shower-washing actions -Body excretory system-Hand-face-foot washing actions-Shaving actions-Making up action-Hair washing and drying action 2. For cleanliness and care of house goods, clothing and covers,-Linen washing and drying action -Cleaning action with cleanliness tools -Storing of cleanliness tools with dirty and clean linens in addition to the above actions;-Cleaning and care of babies and kids-Medical actions can be ordered. Performance criterion's for the purpose of ensuring the physical necessities in baths according to various regulations; can be ordered as lighting system, aeration, heating, security, acoustic. Bath designing, which provides all necessities, is gathered in 4 group; a)Technical necessity, b)Environmental necessity, c)Human necessity, d)Symbolic necessity. Installation, for providing the water and energy necessities of a lot of people who stay at the same place, is defined as the achievement of correct arrangement of the actual technology in the structure. Duties of hygienic installation, have showed changes; due to the progress related to time, white period, one house-one tap, pre comfort and rationaled comfort. Providing clean water, which is backbone of contemporary (modem) civilization level reflecting into structure, conveyance to different function areas with different elements, using in there, disposal after use, providing again transformation to its natural balance with artificial ways and constituting the recycling systems according to the actual conditions; cause a complicated system and give to the applier important responsibilities. Equipment is defined as " The tools and material which improve the user's activity in order to provide a specified action " . Hygienic installation elements, which are equipment's that are being used for the health actions are various according to its functional use areas. The equipment's used for in body care function is defined as; wash basin, and shower bath basin sitting or laying basin and for body excretory system usage, water-closed or toilet. Type and number of hygienic installation equipment's, which will be settled, vary with the number of people and correct settlement of hygienic installation element will make usage easier. Production of solutions of wet volumes, in most economic and practical forms; will be an important development for the building industry, depending on the .increased house necessity nowadays. Préfabrication application types can be ordered as pine préfabrication, packet préfabrication, installation walls, elemented cells, total cells. The results of the researches show that; for the achievement of hygienic installation in wet volumes, twenty items work belonging to eight different job groups should be done. Because of mistakes that are made in planning process or in application, faulty of material used, sudden press increase in installation, wrong usage, settling of the building in time, freezing etc. same trouble can be seen in operation of hygienic installation systems. The investigations show that the actions and the bath place which take place in different scaled houses; depending on social-economic and cultural structure, greatness of house people, user and hygienic installation equipment characteristics; come out in a complicated diversity set. The most satisfactory way, in order to examine the problems and meet the user demands at optimum level for determining how bath place should be like; is making area studies related to the subject. In this point of view an area application study has been made, which involves 30 women as sample; that have been selected from the middle income group. In the research face to face method have been used which is a part of the quantity research technics and the result data have been evaluated with percent, determining frequency and weighted average criterion. In meeting the families house people the range changes between 2-6 people. % 30 of the inquiry participants are from Istanbul. % 50 of the samples prefer their houses because they are pleased with their neighborhood/quarter; %43.3 because of economical situations and lastly %23.3 because they are pleased with their houses The area of the baths changes between 3.1-7.6 m-. The %80 of the samples use bath and wc together. %33.3 has a second wc in their houses. 18 samples who have a basin are pleased with the dimension and the height of basin. According to the area study; in different scaled houses bath areas are not proportional to the house areas. It has been observed that, in design and application phase user dimensions for the activities in bath place, place dimensions and in consequence of this case; the actions that take place in bath area have been shifted to other places. For instance ; doing the washing. It has been determined that ; as a first step the house people make modification in their wet volumes and in the modification phase they prefer and use the equipment and material which belong to their own selections. This case makes thinking of that; in design and application phase user requirements should be primarily considered. It has been determined that in simple bath places, providing the physical necessities, the required performance conditions are not satisfied, aeration of bath which are opened to aeration chimney is in sufficient. Thus other solutions are being looked for aeration. In our country, because it has not been determined user and place dimensions related to activities, place unit area and dimension values, place standards and performance criterion for house baths ; users fall in physical and psychological disquiet while using these places. Because of this reason, firstly user necessity and requirements should be determined according to population clifferent social, economical and cultural structure. When actions in bath place has been investigated, it has been determined that this place is requires so much security and secrecy in house. Consequently in order to achieve these actions healthy the bath places not only with dimensional factors, but also the environmental factors like sighting, aeration, acoustic, heating security should be considered.
The Survey Of The Bath Plant In Middle Quality Houses
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1995
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 1995
Keywords: Banyo; Konut; İç mekan; Bathroom ;Dwelling house ;Interior space